2023
DOI: 10.1590/fst.100722
|View full text |Cite
|
Sign up to set email alerts
|

Steaming and vacuum drying preserve active components, sensory and antioxidant properties of Flos Sophorae

Abstract: Flos Sophorae (FS) is medicinal and edible, while fresh FS is highly perishable. Thus, this study investigated the effects of different drying methods (hot air drying, HAD; vacuum drying, VD; freeze drying, FD) after steaming on the bioactive components and sensory quality of FS. The results indicated steaming for 1 min maximally retained the contents of total flavonoids, rutin, and quercetin in thermal drying (HAD and VD), meanwhile, the freeze-dried FS without steaming also had higher total flavonoids and ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Turkmen et al (2006) showed that boiling and steaming reduced chlorophyll a and chlorophyll b contents, while inducing the appearance of pheophytin a and pheophytin b in cooked vegetables. Guo et al (2023) reported that steaming increased the yellowish color of dried Flos Sophorae. Cooking methods had different effects on color or chlorophyll content due to energy transfer (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Turkmen et al (2006) showed that boiling and steaming reduced chlorophyll a and chlorophyll b contents, while inducing the appearance of pheophytin a and pheophytin b in cooked vegetables. Guo et al (2023) reported that steaming increased the yellowish color of dried Flos Sophorae. Cooking methods had different effects on color or chlorophyll content due to energy transfer (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The quality research of traditional Chinese medicine has been the focus and hot spot of the modernization research of traditional Chinese medicine. Some chemical components of traditional Chinese medicine will change during the storage process and the control of these components that are prone to qualitative and quantitative changes has become the main focus of the quality control of traditional Chinese medicine (Guo et al, 2023;Chen et al, 2023). The chemical composition of the Yanlishuang Pills is complex and easily volatile, and only the joint monitoring of multiple components can achieve quality control of the active ingredients.…”
Section: Establishment Of Fingerprints and Determination Of Various I...mentioning
confidence: 99%
“…The NGB-CFD group exhibited the highest levels of total avonoids and total phenolics due to the unprocessed treatment, which prevented the loss of avonoids during steaming and the CFD, which ensured the maximum retention of active ingredients. Guo et al [19] found that freeze drying of Sophora japonica owers resulted in higher total avonoid content than hot air and vacuum drying. Other studies had shown that heating fresh turmeric resulted in a decrease in total phenolics and total avonoids [11] , reinforcing the ndings.…”
Section: The Contents Of Eight Functional Componentsmentioning
confidence: 99%